Theory of Mind Impairments Highlighted With an Ecological Performance-Based Test Indicate Behavioral Executive Deficits in Traumatic Brain Injury - Allain, Philippe; Hamon, Martin; Saoût, Virginie; Verny, Christophe; Dinomais, Mickaël; Besnard, Jeremy (Frontiers in Neurology, 2020)
Backgroung: In view of the recent literature, the question does not really arise today whether traumatic brain injury (TBI) causes deficits in social cognition abilities. In fact, many studies have reported significant problems in emotion recognition, poorer theory of mind abilities, as well as a decrease in self-reported empathy, difficulties in pragmatic language, moral reasoning and social problem solving in TBI patients. On the other hand, a certain number of questions remains concerning the manner of testing social cognition deficits in these patients and concerning the consequences of these deficits on their social behavior. Objectives: In the present study, 47 moderate-to-severe TBI patients in the chronic stage were assessed with the Movie for the Assessment of Social Cognition (MASC), a film displaying social interactions in natural settings, and asking for an evaluation of the emotions, thoughts and intentions of the characters. Their behavioral problems were assessed with the Behavioral Dysexecutive Syndrome Inventory (BDSI), a structured interview of an informant assessing changes compared with previous behavior in 12 domains. Results: Patients were significantly less accurate in mental state attribution than a matched group of 38 healthy control subjects on the MASC. TBI patients also exhibited significantly more behavioral problems on most of the domains of the BDSI. Impaired social cognition in the MASC was significantly correlated with behavioral dysexecutive problems as rated by proxies on the BDSI. Conclusions: This study is the first to find association between impairments in mentalizing abilities in the MASC and behavioral dysexecutive problems in TBI patients, confirming that the recognition of social signals is a key element for adequate behavioral functioning.